An Optimized DNA Extraction Protocol For Isolation Of High Quality Genomic DNA From Camphor Containing Timber Tree Species, Dryobalanops Beccarii Dyer - Wei-Seng, Ho; Kit-Siong, Liew; Shek-Ling, Pang (IJSTR, 2016)
Isolation of high-quality genomic DNA from Dryobalanops beccarii is obviously difficult due to the existence of large amounts of camphor and other secondary metabolites. These contaminants will co-precipitate with DNA during DNA isolation and purification processes, and therefore, resulting in a brownish DNA pellet that is unsuitable for downstream applications. Many DNA isolation protocols are available for various plant tissues; however these protocols are inefficient in yielding high-quality amplifiable genomic DNA especially from camphor containing timber tree species. A CTAB based protocol has been optimized for isolating genomic DNA from camphor containing timber tree species. Key steps include: 1) using 1% β-mercaptoethanol and 2% PVP 40 (Mr 40,000) in the extraction buffer; 2) sample incubation time, 40 minutes at 65°C, and 3) DNA precipitation at room temperature (25°C). The isolated DNA pellet was transparent colour and the purified genomic DNA is suitable for PCR amplification.